The mediating role of earning management in enhancing firm value - Putry, Nur Anita Chandra; Yuliwantono, Ephing (Proceeding International Conference on Accounting and Finance, 2026)
This paper analyzes the relationship between financial performance, corporate governance, and firm value, considering earnings management as an intermediary variable in ASEAN technology companies during 2021–2024. Using a quantitative approach, this research employed secondary data obtained from company financial reports with a purposive sampling method. The analysis technique employed was multiple regression and a mediation test using SPSS 27 with the PROCESS Macro (Hayes, 5.0) to identify indirect effects. The empirical results show that profitability has a significant impact on firm value, whereas managerial ownership does not exhibit a significant effect. Furthermore, earnings management mediates the relationship between managerial ownership and firm value but does not significantly mediate the relationship between profitability and firm value. These findings highlight the role of earnings management in strengthening or weakening the effects of financial performance and corporate governance on firm value.